Study of Soil Erodibility in Various Agroforestry Systems Based on Elephant Foot Yam (Amorphophallus oncophyllus) in Bayan District, North Lombok Regency - Rudy Fermana; I Gusti Made Kusnarta; Padusung (Jurnal Biologi Tropis, 2023)
Bayan District has a wavy to mountainous topography. The type of soil in the area is classified as Inceptisol, so it is very susceptible to erosion. An agroforestry system, with various stands of perennial crops, has been developed in the area, as a conservative measure to support the sustainability of land resources. This study aims to assess the value of soil erodibility in Elephant foot yam-based agroforestry systems in five types of stands, namely: Teak (A1), Cashew (A2), “Gamal” and Banana (A3), Cocoa (A4), and Coffee (A5). The method used is descriptive method with survey technique. Determination of the research location was carried out by purposive sampling with the criteria of land having a rather steep slope (15-17%), the soil order Inceptisol, located in the upper slope, and a high level of stand vegetation homogeneity.  Soil samples (undisturbed and disturbed) were collected using the diagonal method on 10 x 10 m plots randomly placed in each agroforestry system with a depth of 0-20 cm. Parameters observed were soil texture (pipette method), soil permeability (constant head), soil structure (qualitative in the field), and soil organic matter (Walkley and Black). The result showed that the value of soil erodibility, in agroforestry systems with different stands, was significantly difference, with the lowest value was found in the Coffee agroforestry system (A5) of 0,416 and the highest was found in the Cashew system (A2) of 0,661. The effectiveness of improvement soil erodibility in the agroforestry system of A5 was 37% better than A2.